Decrease in search to hospitals and health services and the interruption of therapeutics and treatments during pandemic. - Barros, Gabriela; de Souza Louver , Gabriella; Valentin Barros , Giulia; Cristina Barros Teixeira , Layla; Alves Christensem Pereira , Larissa; Mautoni Marcondes Machado , Melissa; de Barros Marinho , Natália; Oliveira, Leonardo (Brazilian Journal of Global Health, 2021)
OBJETIVO: O objetivo deste trabalho foi avaliar o impacto da pandemia COVID-19 na procura por serviços de saúde a partir de quatro critérios (cancelamento de consultas médicas, suspensão de tratamentos, adiamento de cirurgias e a não realização de exames de rotina), comparando os resultados entre gêneros e faixas etárias. MÉTODOS: Foi realizado um levantamento por meio de um questionário via internet em outubro de 2020. RESULTADOS: Foram obtidas 602 respostas, em que mulheres apresentaram menores taxas de ida aos serviços de saúde em comparação aos homens e, os indivíduos pertencentes à faixa etária idosa cancelaram mais consultas médicas, interromperam mais terapêuticas, adiaram mais cirurgias do que as outras faixas etárias. CONCLUSÃO: Ao considerar a visão geral de todas as faixas etárias, a pandemia causou uma diminuição em cerca de 28% na procura por consultas médicas sendo esta diminuição mais significativa entre idosos e mulheres. Estes resultados enfatizam a necessidade de campanhas específicas para estes públicos em períodos de isolamento social devido às pandemias. DESCRITORES: Isolamento social, Coronavirus. ABSTRACT OBJECTIVE: The objective of this study was to evaluate the impact of the COVID-19 pandemic over the search for healthcare services according to four criteria (cancellation of medical consultations, suspension of treatments, postponement of surgeries and non-performance of routine tests), comparing the results between genders and age groups. METHODS: A survey was conducted through an internet questionnaire in October 2020. RESULTS: 602 responses were obtained, and the results were that women had lower rates of going to health services compared to men and individuals belonging to the elderly age group canceled more medical visits, interrupted more therapies, and postponed more surgeries than other age groups. CONCLUSION: Considering the overview of all age groups, the pandemic caused a decrease of about 28% in the demand for medical consultations and this decrease is more significant among the elderly and women. These results emphasize the need for specific campaigns for these people in periods of social isolation due to the pandemics. DESCRIPTORS: Social isolation, Coronavirus.